Two new rove beetle species from China (Coleoptera, Staphylinidae) - Huang, Jia-Yi; Tang, Liang; Li, Li-Zhen (Zootaxa, 2025)
Two new rove beetle species from China are described: Stenus yintiaolingus Huang, Tang & Li, sp. nov. from Chongqing and Parabolitobius zhejiangensis Huang, Tang & Li, sp. nov. from Zhejiang. And the diagnostic characters of both new species are illustrated.